Rancang Bangun Teologi Spiritual Dalam Pembentukan Spiritualitas Orang Percaya - Royke Lontoh (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2022)
The purpose of writing this article is to design a spiritual theology that can be used as a basis for practicing the spirituality of a believer's life. Conduct an assessment of the spirituality of a believer's life that departs from the understanding of theology he adheres to. The method used is literature study to explain and answer the problem formulation in this study. Spiritual theology guides people to have a close relationship with Allah, uniting humans with their Creator. From the point of view of Christian faith, spiritual theology raises awareness for every believer to live according to the truth of God's Word, achieve a spiritual life that is good, moral, and has spiritual intelligence according to the stages of his development. Spiritual theology teaches that something of value is considered valuable, has meaning in all aspects of life, including all creatures and the universe. This will shape each person's personality to have love and concern for the preservation of all creatures and nature. Spiritual theology among Pentecostals-Charismatics talks about an intimate relationship with God; experiencing fellowship with the Holy Spirit through baptism living under the guidance and sanctification of the Holy Spirit, and Receiving the gifts of the Spirit to serve with the anointing and power of God. ABSTRAK BAHASA INDONESIA Tujuan penulisan artikel ini adalah sebagai rancang bangun teologi spiritual yang dapat dijadikan dasar praktik spiritualitas kehidupan orang percaya. Melakukan penilaian terhadap spiritualitas kehidupan orang percaya yang berangkat dari pemahaman teologi yang dianutnya. Metode yang digunakan adalah studi literatur untuk menjelaskan dan menjawab rumusan masalah dalam penelitian ini. Teologi spiritual membimbing orang untuk memiliki hubungan yang dekat dengan Allah, menyatukan diri manusia dengan Penciptanya. Dari sisi iman Kristen teologi spiritual memunculkan kesadaran kepada setiap orang percaya untuk hidup sesuai dengan kebenaran Firman Tuhan, mencapai kehidupan spiritual yang baik, bermoral, dan memiliki kecerdasan spiritual yang sesuai dengan tahapan perkembangannya. Teologi spiritual mengajarkan sesuatu yang bernilai dianggap berharga, memiliki makna dalam semua aspek kehidupan, termasuk semua makhluk dan alam semesta. Hal ini akan membentuk pribadi setiap orang memiliki kecintaan dan kepedulian terhadap kelestarian semua mahluk dan alam. Teologi Spiritual di kalangan Pentakostal-Kharismatik berbicara tentang hubungan yang intim dengan Tuhan; mengalami persekutuan dengan Roh Kudus melalui baptisan hidup dalam bimbingan dan pengudusan oleh Roh Kudus, dan Menerima karunia Roh untuk melayani dengan urapan dan kuasa Tuhan.